Literasi Keuangan Syariah bagi Pelaku UMKM di Bandar Lampung - Nindytia Puspitasari Dalimunthe; Lidya Ayuni Putri; Mutiasari Nur Wulan (Jurnal Pemberdayaan Ekonomi, 2023)
Purpose: The purpose of this activity is to increase the literacy of MSME actors in Bandar Lampung about Sharia financial. Method: The methodology in this activity is lecture and discussion. The Unila FEB team made a presentation on syaria finance contracts and a discussion session was held at the end of the session. Results: There is an increase in participants' knowledge from 40 to 75. This indicates an increase in sharia financial literacy for participants. Conclusions: This service activity has been carried out with a total of 20 participants. The results of this socialization are expected to provide additional knowledge and experience for MSME actors which can be seen from the results of the pre-test and post-test. During the activity, the participants looked enthusiastic and enthusiastic in asking questions. Limitations: this activity only discuss about contracts (akad) that implemented in financial. Contribution: Increasing Sharia financial literacy for MSME actors in Bandar Lampung.